Di-aeolotropic electric conductive Janus nanobelts with up-/down-converting fluorescence and magnetism by sequential coaxial and side-by-side electrospinning. (November 2022) - Yang, Xiuling; Qi, Haina; Jiang, Shaohua; Dong, Xiangting; Duan, Gaigai
Abstract: Di-aeolotropic conductive left-to-right structured special Janus array membrane (SJ-J-AM) simultaneously with up-/down-converting fluorescence and magnetism was built via electrospinning. SJ-J-AM consists of {[CoFe2 O4 /polymethylmethacrylate (PMMA)@[poly(3, 4-ethylenedioxythiophene) (PEDOT)/PMMA]}//[NaYF4 :Yb 3+, Er 3+ /PMMA] special Janus array film with up-converting luminescence (UL) as left-side (U-SJAF) and [PEDOT/PMMA]//[Tb(acac)3 bipy/PMMA] Janus array film with down-converting luminescence (DL) as right-side (D-JAF). Microscopically, Janus nanobelt with concentric//uniaxial structure and common Janus nanobelt, as building unit, efficaciously confines functional substances to their respective area, averting reciprocal affect among conduction, magnetism and luminescence to earn enhanced fluorescence and strong aeolotropic conduction, the luminescence intensity of U-SJAF and D-JAF are respectively 6.2 and 7 times than that of composites array film with UL and DL. Macroscopically, SJ-J-AM fulfills the portion of UL and DL regions, and the tight connection between U-SJAF and D-JAF with single aeolotropism conductance makes SJ-J-AM to hold di-aeolotropic conduction, realizing the high integration of micro- and macro-portion in SJ-J-AM. Graphical abstract: Image 1 Highlights: Janus membrane has dual-mode fluorescence, di-aeolotropic conduction and magnetism. Partition of three independent portions in Janus film is macroscopically actualized. Partition of two independent regions in Janus nanobelt is microscopically realized. Macro- and micro-partition are concurrently realized in the exceptive Janus membrane. Partitioned structure helps to reduce adverse interactions among various materials.